Studying literary theory : an introduction - Webster, Roger, 1950- (London : Arnold, 1996)
In recent years, the discipline of English has become increasingly problematic as a field of academic study. What kinds of text constitute 'English literature', and how they might be read, interpreted and analysed are no longer straightforward issues. In particular, the impact of modern literary theory since the 1980s has revolutionized the ways in which we now think about literature, investigating many areas hitherto considered unquestionable or self-evident.
This new second edition builds on the previous edition in several ways. Like its predecessor, it provides an accessible introductory guide to some of the most important aspects of literary theory, linking them to more traditional terms and approaches to ensure that the areas discussed are not wholly unfamiliar territory.
In doing so, it offers a fuller introduction to a wider range of literary theories, including poststructuralism, postmodernism, New Historicism, postcolonial theory and theories of sexual identity. Discussion of other theories is revised and extended and additional illustrative material indicates how aspects of theory might be applied to various texts.
1. Points of departure -- 2. What is literary theory? -- 3. Language and narrative -- 4. 'Society' and the 'individual' -- 5. Textual relations -- 6. Further reading.
Includes bibliographical references (p. [131]-135) and index.
Keywords: Criticism -- Study and teaching